Effect of facial presence in user-generated photos on intention to purchase restaurant foods: an experimental study from vietnam - Tran Thi Tuyet; Vu Thi Thu Huyen; Viet Thai Nguyen (Cogent Business & Management, 2024)
As online activities related to purchasing restaurant foods have become more common, user-generated photos (UGPs), including a customer's face, have emerged as crucial sources of information because they offer a better visual cue and create a higher level of trust, subsequently increasing purchase intention. However, little research has examined the effect of facial presence in UGPs on customers' purchase behavior in restaurants in Vietnam. This study aims to investigate the relationship between facial presence in UGPs and purchase intention while simultaneously testing the mediating role of trust. A two-group design was used, with one group featuring UGPs with facial presence and the other UGPs without facial presence. Results indicate that participants in the UGPs with facial presence condition exhibited a higher level of trust and, hence, a greater purchase intention than those in the UGPs without facial presence condition. These findings expand our understanding of UGPs and purchase intention and provide restaurant managers with valuable practical implications.
Keywords: 650; Purchase intentions; user-generated photos; facial presence; online restaurant review; heuristic-systematic model; source credibility